2020
DOI: 10.7570/jomes20002
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Pediatric Overweight and Obesity in Korea

Abstract: Over the previous decades, the prevalence of pediatric obesity has been increased in Korea as well as worldwide. Pediatric obesity is associated with comorbidities in childhood and adulthood. We reviewed the prevalence of pediatric obesity using data from the National School Health Examination (NSHE) and the Korea National Health and Nutrition Examination Survey (KNHANES). Obesity was defined as a body mass index (BMI) ≥25 kg/m 2 ; BMI ≥95th percentile for the corresponding sex and age in the 2007 growth chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
2
52
0
Order By: Relevance
“…A recent multinational study reported that up to 30% of children and adolescents with T1D were overweight or obese 42 . In this study, 21% of T1D patients were overweight and/or obese 5 years after the diagnosis, similar to the frequency in the general population of Korea 43 . Because obesity has become a common problem in children and adolescents with T1D, monitoring BMI during the treatment course should be emphasized as a key component of pediatric T1D care.…”
Section: Discussionsupporting
confidence: 82%
“…A recent multinational study reported that up to 30% of children and adolescents with T1D were overweight or obese 42 . In this study, 21% of T1D patients were overweight and/or obese 5 years after the diagnosis, similar to the frequency in the general population of Korea 43 . Because obesity has become a common problem in children and adolescents with T1D, monitoring BMI during the treatment course should be emphasized as a key component of pediatric T1D care.…”
Section: Discussionsupporting
confidence: 82%
“…Given that the trend of AAM in Korea over generations are more dramatically decreased compared to that in western countries and similar patterns are observed worldwide in generational prevalence of childhood obesity [57][58][59], generational trend of AAM in Korea is not thought to be only caused by increasing childhood obesity. The gap between the trend of AAM and childhood obesity make it necessary to consider the generation effect in the study of causal association between AAM and young adulthood BMI.…”
Section: Plos Onementioning
confidence: 63%
“…The prevalence of obesity increased twice (8.7% to 15.0%) during 10 years (2007 to 2017) in children aged 6–18 years [ 15 ]. The prevalence of overweight/obese children aged 2–19 increased from 1998 to 2012, from 15.2% to 25.5% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%